2008
DOI: 10.1007/s00381-008-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

Repair process in spontaneous intradural dissecting aneurysms in children: report of eight patients and review of the literature

Abstract: Spontaneous resolution of intradural dissecting aneurysm with or without parent artery occlusion is not uncommon even in the pediatric population. Aneurysm repair is a dynamic and multifaceted entity. Mural hematoma appears to be the most important factor promoting thrombosis and healing of the dissecting intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In dissecting aneurysms, mural hematoma seems to be the most important promoting factor for spontaneous thrombosis and healing of the aneurysm [21]. …”
Section: Treatmentmentioning
confidence: 99%
“…In dissecting aneurysms, mural hematoma seems to be the most important promoting factor for spontaneous thrombosis and healing of the aneurysm [21]. …”
Section: Treatmentmentioning
confidence: 99%
“…Koroknay-Pal et al (24) and Liang et al (25) also reported the same phenomenon. A mural hematoma appears to be the most important promoting factor for spontaneous thrombosis and healing of aneurysms (4). …”
Section: Discussionmentioning
confidence: 99%
“…Giant aneurysms are relatively common among pediatric patients with intracranial aneurysms (3). There have been few reports on children with IDAs (4, 5). This study aimed to analyze the clinical presentation, aneurysm characteristics, and treatment outcome of IDAs in patients aged 18 years or younger at our center over the last 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, procedures such as parent-artery occlusion that promote mural thrombosis are often required for the treatment of dissecting aneurysms. However, dissecting aneurysms occasionally disappear because of progressive thrombosis of the aneurysmal sac or parent-artery lumen 2,21 . In adults, 18.3% of intracranial arterial dissections showed complete normalization between 15 days and two months following presentation with symptoms on neuroimaging follow-up, but these are non-ruptured cases 21 .…”
Section: Case Reportmentioning
confidence: 99%